Concordance of biopsy and pathologic ISUP grading in salvage radical prostatectomy patients for recurrent prostate cancer. Issue 2 (22nd November 2021) - Preisser, Felix; Würnschimmel, Christoph; Pose, Randi M.; Heinze, Alexander; Steuber, Thomas; Michl, Uwe; Salomon, Georg; Mandel, Philipp; Graefen, Markus; Tilki, Derya
Abstract: Purpose: To investigate the concordance of biopsy and pathologic International Society of Urological Pathology (ISUP) grading in salvage radical prostatectomy (SRP) patients for recurrent prostate cancer. Methods: Within a high‐volume center database, we identified patients who underwent SRP for recurrent prostate cancer (PCa) between 2004 and 2020. Upgrading, downgrading, concordance, and any discordance between posttreatment biopsy ISUP and ISUP at SRP were tested. Logistic regression models were used to predict ISUP upgrading and ISUP discordance. Models were adjusted for prostatic specific antigen before SRP, age at surgery, initial prostatic specific antigen (PSA), type of primary treatment, time from primary PCa diagnosis to SRP, number of positive cores at biopsy, and original Gleason score. Results: Overall, 184 patients with available biopsy and pathologic ISUP grading were identified. Of those, 17.4% ( n  = 32), 40.8% ( n  = 75), 19.6% ( n  = 36), and 22.2% ( n  = 41) harbored biopsy ISUP 1, ISUP 2, ISUP 3, and ISUP 4–5 grading, respectively. Pathologic ISUP 1, ISUP 2, ISUP 3, and ISUP 4–5 grading was recorded in 6.0% ( n  = 11), 40.8% ( n  = 75), 32.1% ( n  = 59), and 21.2% ( n  = 39), respectively. Median PSA before SRP was 5.5 ng/ml (interquartile range [IQR]: 3.1–8.1 ng/ml), median age at SRP was 65.1 years (IQR:60.7–69.4 years) and median time from original PCa diagnosis to SRP was 47 months (IQR: 27.3–85.2 months). Concordance of biopsy and pathologic ISUP was identified in 45.1% ( n  = 83). Conversely, any ISUP discordance, upgrading and downgrading of at least one ISUP group was identified in 54.9% ( n  = 101), 35.3% ( n  = 65), and 19.6% ( n  = 36). In logistic models, none of the preoperative characteristics was associated with upgrading or ISUP discordance (all p  > 0.1). Conclusion: Discordance between biopsy and pathologic ISUP grading is common at SRP. However, in 45% of SRP cases biopsy ISUP is capable to predict pathologic ISUP. Further studies are necessary to identify characteristics for ISUP upgrading at SRP.